Concerted activation of the AIM2 and NLRP3 inflammasomes orchestrates host protection against Aspergillus infection - Karki, Rajendra (Cell Host Microbe, 2015)
Invasive pulmonary aspergillosis is a leading cause of infection-associated mortality in immunocompromised individuals. Aspergillus fumigatus infection produces ligands that could activate inflammasomes but the contribution of these host defenses remains unclear. We show that two inflammasome receptors, AIM2 and NLRP3, recognize intracellular A. fumigatus and collectively induce protective immune responses. Mice lacking both AIM2 and NLRP3 fail to confine Aspergillus hyphae to inflammatory foci, leading to widespread hyphal dissemination to lung blood vessels. These mice succumb to infection more rapidly than WT mice or mice lacking a single inflammasome receptor. AIM2 and NLRP3 activation initiates assembly of a single cytoplasmic inflammasome platform, composed of the adaptor protein ASC along with caspase-1 and caspase-8. Combined actions of caspase-1 and caspase-8 lead to processing of proinflammatory cytokines IL-1β and IL-18 that critically control the infection. Thus, AIM2 and NLRP3 form a dual cytoplasmic surveillance system that orchestrates responses against A. fumigatus infection.